The Institutions of programmatic action: policy programs in French and German health policy - Hornung, Johanna (International Series on Public Policy, 2022)
Chapter 1: Introduction -- Chapter 2: Programmatic Action and Policy Processes -- Chapter 3: Political Institutions and Public Policy -- Chapter 4: Health Policy Institutions in France and Germany -- Chapter 5: Programmatic Action in French Health Policy -- Chapter 6: Programmatic Action in German Health Policy -- Chapter 7: The Institutions of Programmatic Action -- Chapter 8: Conclusion.